2008
DOI: 10.1007/s12185-008-0144-x
|View full text |Cite
|
Sign up to set email alerts
|

Current status of Japanese HIV-infected patients with coagulation disorders: coinfection with both HIV and HCV

Abstract: We herein report on the current status of Japanese HIV-positive patients with coagulation disorders, primarily hemophilia, based on the national survey of 31 May 2006. The total number of registered patients was 1,431 (Hemophilia A 1,086; Hemophilia B 325; von Willebrand disease 8; others 12), and 604 of these patients were deceased by 31 May 2006. The survival rate after the beginning of 1983 was evaluated by the Kaplan-Meier method. The total number of surviving patients was 827, and the survival rate on 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In this context, it is hoped that more and more hemophilia A patients and their treating doctors will demand that the hemophilia community answer these questions through randomized studies, rather than through competing expert opinions or through political decisions that allocate limited resources. For example, is the quality of life of adult hemophilia A patients better using the graduated escalating frequency of infusions to prevent most spontaneous bleeding or using the regular infusion schedule of every other day to prevent essentially all spontaneous bleeding?34,35 Do the medical complications outweigh the benefits?36,37 What additional therapies are beneficial when treating the complications of severe hemophilia A?3841 Comparison data from clinical trials will be important to guide appropriate decisions for where and how society should allocate its health care resources 42…”
Section: Current Treatment For Hemophilia Amentioning
confidence: 99%
“…In this context, it is hoped that more and more hemophilia A patients and their treating doctors will demand that the hemophilia community answer these questions through randomized studies, rather than through competing expert opinions or through political decisions that allocate limited resources. For example, is the quality of life of adult hemophilia A patients better using the graduated escalating frequency of infusions to prevent most spontaneous bleeding or using the regular infusion schedule of every other day to prevent essentially all spontaneous bleeding?34,35 Do the medical complications outweigh the benefits?36,37 What additional therapies are beneficial when treating the complications of severe hemophilia A?3841 Comparison data from clinical trials will be important to guide appropriate decisions for where and how society should allocate its health care resources 42…”
Section: Current Treatment For Hemophilia Amentioning
confidence: 99%
“…reported that 19.2% of HIV patients were positive for the anti‐HCV antibody, and most of them were recipients of blood products . Another study indicated that 98% of Japanese HIV‐infected patients with coagulation disorders were positive for the anti‐HCV antibody, whereas in HIV‐positive men‐who‐have‐sex‐with‐men, the HCV prevalence was approximately 4% . Recently, aspartate transaminase–platelet ratio and Fibrosis‐4 indices or albumin–indocyanine green evaluation were shown to effective markers for monitoring esophageal varices in patients with HCV/HIV coinfection due to contaminated blood products for hemophilia.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophilia increases the risk of co-infection with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) due to contaminated or unheated blood products (1,2). According to a survey by the National Institute of Infectious Diseases, 1,431 hemophilia patients in Japan were infected with HIV due to contaminated or unheated blood products and 95% were co-infected with HCV (HIV/HCV co-infected).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that co-infection with HIV/HCV is associated with a greater rate of rapid progression to liver cirrhosis and end-stage liver disease (2)(3)(4)(5). Additionally, several studies have reported that the prognosis of hemophilia patients co-infected with HIV/HCV has continued to improve along with advancements in highly active anti-retroviral therapy for HIV (6)(7)(8), resulting in a shift in the leading cause of death to HCV-associated end-stage liver disease (1,2,9,10). Therefore, the degree of liver dysfunction mainly affects the prognosis of co-infected hemophilia patients.…”
Section: Introductionmentioning
confidence: 99%